Écriture de cas entre stagiaires, étudiants de pédagogie et leurs tuteurs, professeurs en exercice : un dispositif pour la professionnalisation enseignante - Mauricio Núñez Rojas (Université de Provence, 2015)
Professionalization among teachers is a lifetime construction. However, it is generally organized in two separate learning pathways: initial and continuing training. We believe that, beyond the differences between these two paths, we could intentionally open a point of convergence between them, in order to mutually nurture the experience of novice and experienced teachers. We propose a collaborative research, supported by reflective action: a case writing workshop. Through this action, a group of teachers constituted by preservice teachers and their mentors begin to build a paritarian community of practice, investigation and writing. Thus, individual and collective professional experience will be co-constructed. The idea of bringing toghether the training routes of those who are at the begining of their career and those who have several years of teaching practice (in order to produce an intergenerational dialogue that would help to question, problematize and enrich the experience of novices and experienced teachers), is revealed in all its power of transformation as a professionalization device.